Virtual implantations to transition from porcine to bovine animal models for a total artificial heart. Issue 4 (12th November 2019) - Sonntag, Simon J.; Meyns, Bart; Ahn, Henrik C.; Pahlm, Fredrik; Hellers, Göran; Najar, Azad; Pieper, Ina Laura
Abstract: Realheart total artificial heart (TAH) is a novel, pulsatile, four‐chamber total artificial heart which had been successfully tested acutely in a porcine animal model. However, the bovine model is better suited for long‐term testing and thus an evaluation of how the design would fit the bovine anatomy was required. Virtual implantation is a method that enables a computer simulated implantation based on anatomical 3D‐models created from computer tomography images. This method is used clinically, but not yet adopted for animal studies. Herein, we evaluated its suitability in the redesign of the outer dimensions and vessel connections of Realheart TAH to transition from the porcine to the bovine animal model. Virtual implantations in combination with bovine cadaver studies enabled a series of successful acute bovine implantations. Virtual implantations are a useful tool to replace the use of animals in early device development and refine subsequent necessary in vivo experiments. The next steps are to carry out human virtual implantations and cadaver studies to ensure the design is optimized for all stages of testing as well as the final recipient.